2009
DOI: 10.1016/s1053-8119(09)70744-x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence for the selective subcortical degeneration in Huntington's disease

Abstract: Although Huntington's disease is largely considered to be a subcortical disease, there is no clear consensus on whether all deep grey matter loss is a direct downstream consequence of the massive degeneration of the medium-size spiny neurons in the striatum. Our aim was to characterise in vivo such preferential degeneration by analysing various distinct diffusion imaging measures including mean diffusivity, anisotropy, fibre orientation (using the information of the principal diffusion direction) and white mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 25 publications
6
56
0
1
Order By: Relevance
“…We also found increased FA and MD in the caudate nucleus and the putamen bilaterally, in line with the higher MD [Douaud et al, 2009;Henley et al, 2009;Mascalchi et al, 2004] and FA [Douaud et al, 2009] reported in both HD and presymptomatic gene carriers [Rosas et al, 2006]. FA increase in the striatum and globus pallidus was attributed to a decreased dispersion of fiber orientation, with a preferential loss of connections along specific radiating directions from the striatum while other fibers were relatively spared [Douaud et al, 2009].…”
Section: Discussionsupporting
confidence: 86%
“…We also found increased FA and MD in the caudate nucleus and the putamen bilaterally, in line with the higher MD [Douaud et al, 2009;Henley et al, 2009;Mascalchi et al, 2004] and FA [Douaud et al, 2009] reported in both HD and presymptomatic gene carriers [Rosas et al, 2006]. FA increase in the striatum and globus pallidus was attributed to a decreased dispersion of fiber orientation, with a preferential loss of connections along specific radiating directions from the striatum while other fibers were relatively spared [Douaud et al, 2009].…”
Section: Discussionsupporting
confidence: 86%
“…Despite the structural changes in HD tissue, we have not seen a significant change in the diffusion anisotropy among matched axes between HD and WT mice. In contrast, other studies report an increased FA in the GP (Douaud et al, 2009;Antonsen et al, 2013). Douaud and colleagues (2009) proposed that increased FA in striatal gray matter structures is due to the loss of efferent fibers, which in turn leads to increased coherence.…”
Section: Discussionmentioning
confidence: 94%
“…A number of quantitative magnetic resonance (MR) studies on HD patients and mouse models of HD have used diffusion-weighted magnetic resonance (DW-MR) for assessing gray matter changes (Rosas et al, 2006;Seppi et al, 2006;Douaud et al, 2009;Sanchez-Castaneda et al, 2013), with more and less inconsistent results. DW-MR describes the molecular aspects of water diffusion, which consequently leads to information about tissue microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Dumas et al [2012] has observed more widespread microstructural deficits in white matter pathways of the prefrontal cortex in symp-HD. Increased diffusivity in frontal and parietal white matter, together with higher diffusivity in prefrontal afferents to the putamen has also been reported in HD [Douaud et al, 2009]. Moreover, Klö ppel et al [2008] reported reduction of DLPFC projections to posterior parts of the striatum in pre-HD, compared with controls.…”
Section: Introductionmentioning
confidence: 92%